A Training Simulator for Fractional Dilation and Curettage With Visualized Force-Position Feedback and Quantitative Evaluation. Issue 1 (July 2021) - Zheng, Yijia; Wang, Kaile; Zhang, Kai; An, Jian; Wu, Junjie; Feng, Zhiheng; Liu, Chunlan; Wang, Jianliu; Lu, Qun; Zhang, Jue
Abstract : BACKGROUND: Dilation and curettage (D&C) is a basic, but important procedure with many applications in obstetrics and gynecology. Fractional D&C provides comprehensive sampling of the endocervix and subsequently the uterus. This study designs and validates a novel fractional D&C training simulator visualizing the intrauterine operation in real time and quantitatively assessing technical skills. METHOD: The fractional D&C training simulator, consisting of measurement hardware and visual software, can display the curette tip's trajectory and force in the uterus in real time. The simulator also presents assessment indices (the cervical coverage index, cervical overlap index, uterine coverage index, uterine overlap index) to indicate the completion degree and quality of surgical performance. EXPERIENCE: Seventy-five participants with three levels of D&C experience, including 26 novices, 24 intermediates, and 25 experts, were recruited to perform fractional D&C using the training simulator and asked to fill in a postprocedure questionnaire. All assessment indices of the novices were significantly lower than those of experienced surgeons (experts and intermediates) ( P <.05). The simulator was highly regarded as a teaching tool and identified frequent areas of incomplete curettage even by experienced surgeons. CONCLUSION: The fractional D&C training simulator provides valuable visualized force-position feedback and quantitative evaluation and may be beneficial for surgical training. Abstract : A training simulator can offer visualized force-position feedback and objective evaluation of fractional dilation and curettage.